The Eighteenth century woman - Baumon, Suzanne; Burroughs, Jun; Slobagin, Kathy; Stella, Pamela (ABC Video Enterprises, 1982)
Looks at an exhibit at New York's Metropolitan Museum of Art entitled the Eighteenth Century woman, a vast collection of costume, accessoriesand jewerly. An object d'art that revealed the unique ways in which fashionable eighteenth century women their presence felt in the society,a rt and politics